2016
DOI: 10.1245/s10434-016-5133-3
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of microRNA-132 is Associated with Poor Prognosis of Colorectal Cancer

Abstract: BackgroundGiven the role of microRNA in colorectal cancer (CRC) progression, we explored the association between microRNA (miRNA) expression and CRC-related prognosis.Methods Three types of tissue samples (primary CRC lesions without liver metastasis, primary lesions with liver metastasis, and liver metastatic tissues) were used for miRNA profiling to identify differentially expressed miRNA. Quantitative real-time PCR was used to examine miRNA expression in CRC cells and in tumor tissues.Results MiR-132 was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 24 publications
0
64
0
1
Order By: Relevance
“…Our group also reported that miRNA-132 was related to liver metastasis of CRC and targets anoctamin 1 (ANO1) (16). In an effort to identify another novel miRNA related to liver metastasis, we focused on miR-487b that significantly decreased in liver metastatic lesions as compared to primary tumors without metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our group also reported that miRNA-132 was related to liver metastasis of CRC and targets anoctamin 1 (ANO1) (16). In an effort to identify another novel miRNA related to liver metastasis, we focused on miR-487b that significantly decreased in liver metastatic lesions as compared to primary tumors without metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Luciferase activity was measured using Dual Luciferase Reporter assay system (Promega), as described previously (16,23). Briefly, the cell extracts were prepared by rinsing each plate twice with PBS and lysing the cells in Passive Lysis buffer (Promega).…”
Section: Quantitative Real-time Polymerase Chain Reaction (Qrt-pcr)mentioning
confidence: 99%
See 2 more Smart Citations
“…The cell invasion assay was carried out using Transwell inserts with 8-lm pores (BD Biosciences, San Jose, CA, USA), based on the manufacturer's protocol and previous reports. (26,27) Cells were seeded into inserts for 24-well plates at 4 9 10 4 cells per insert in serum-free medium and then transferred to wells filled with the culture medium containing 10% FBS. After 24 h incubation, non-invading cells on the top of the membrane were removed by cotton swabs.…”
Section: Methodsmentioning
confidence: 99%